Meningkatkan Hasil Belajar Bahasa Indonesia Menggunakan Blended Learning Basic Remote Model Pada Siswa Kelas VI MI Hidayatul Mubtadiin Sukorame - Wahyu Arif Prasetiawan Maduretno (Jurnal Ilmiah Nizamia, 2022)
This study aims to find out the activities and learning outcomes of students of grade VI MI Hidayatul Mubtadiin Sukorame in The Indonesian Language Subjects 2020/2021. In this study, 19 grade VI students were selected as research subjects. Data collection using test methods and observation methods. Data analysis in this study uses descriptive analysis that interprets qualitative and quantitative data. The results showed that: (1) There was an increase in the average percentage of student learning activities by 14%, from 63 in the less active category of cycle I to 77 or in the active category in cycle II, (2) There was an 8% increase in the average percentage of teacher activity, from 84 in either category in cycle I to 92 or in the excellent category in cycle II, (3) There was an increase in the average percentage of student learning outcomes by 21% from 63 in cycle I to 84 in cycle II. Thus, it can be concluded that the blended learning basic model during the covid-19 pandemic can improve activities and learning outcomes Indonesia subjects in class VI MI Hidayatul Mubtadiin Sukorame students.